A Bibliometric Analysis of Triptolide and the Recent Advances in Treating Non–Small Cell Lung Cancer - Yang, Quancheng; Zhai, Xuejia; Lv, Yi (Frontiers in Pharmacology, 2022)
In recent decades, natural products derived from plants and their derivatives have attracted great interest in the field of disease treatment. Triptolide is a tricyclic diterpene extracted from Tripterygium wilfordii, a traditional Chinese medicine, which has shown excellent therapeutic potential in the fields of immune inflammation and cancer treatment. In this study, 1,106 Web-of-Science-indexed manuscripts and 1,160 Chinese-National-Knowledge-Infrastructure-indexed manuscripts regarding triptolide published between 2011 and 2021 were analyzed, mapping the co-occurrence networks of keywords and clusters using CiteSpace software. The research frontier and development trend were determined by keyword frequency and cluster analysis, which can be used to predict the future research development of triptolide. Non–small cell lung cancer (NSCLC) is most common in lung cancer patients, accounting for about 80% of all lung cancer patients. New evidence suggests that triptolide effectively inhibits the development and metastasis of NSCLC by the induction of apoptosis, reversion of EMT, and regulation of gene expression. Specifically, it acts on NF-κB, MAPKs, P53, Wnt/β-catenin, and microRNAs (miRNAs), signaling pathways and molecular mechanisms. Consequently, this article reviews the research progress of the anti-NSCLC effect of triptolide. In addition, attenuated studies on triptolide and the potential of tumor immunotherapy are also discussed.